Crystal plasticity modeling for grain size and texture effects on laser shock clinching of ultra-thin foils - Yaxuan Hou; Zhong Ji; Haiming Zhang (Journal of Materials Research and Technology)
This paper presents a unified crystal plasticity model for the ultra-high strain rate laser shock clinching (LSC) process of ultra-thin foils by integrating the thermal activation theory, dislocation drag effect and dislocation density evolution. Simulations employing the crystal plasticity finite element method (CPFEM) are conducted to investigate the effects of grain size and initial texture of copper foils during the LSC process after validation by experimental comparisons. The results show that greater strain in copper foils occurs in the region contacting the inner wall of the perforated sheet. The strain evolution follows a consistent pattern independent of grain size: an initial rapid rise in an extremely short time, followed by a continuous rise at about 0.1/μs, peaking around 1 μs post-laser impact and then stabilizing. Notably, joints with fully random crystal orientations exhibit greater thinning rates near the bottom corner and greater neck thicknesses for grain sizes of 75 μm and 30 μm. In contrast, the 10 μm grain size joint exhibits the most uniform deformation with the lowest thinning rate and neck thickness. This is attributed to heterogeneous deformation caused by local incompatibilities between misoriented grains, especially pronounced in larger grain size models. Additionally, six target material textures are examined, indicating that the initial material texture affects the formation of the LSC joint profile. Material textures with more dispersed and less inclined crystal orientations yield superior LSC joints.